Chemical tapering of polymer optical fiber - Abdul Rashid A.R.; Nasution A.A.; Suranin A.H.; Taib N.A.; Mukhtar W.M.; Ahmad Dasuki K.; Ehsan A.A. (EDP Sciences, 2024)
Polymer optical fibers (POFs) have significant advantages over numerous sensing applications. The key element in developing sensor is by removing the cladding of the fiber. The use of organic solvent is one of the methods to create tapered POF in order to expose the core region. In this study, the etching chemicals involved is acetone, methyl isobutyl ketone (MIBK), and acetone-methanol mixture. The POF is immersed in 100%, 80%, and 50% of acetone and MIBK dilution. In addition, the mixture of acetone and methanol is also used for POF etching by the ratio 2:1 of the volume. Acetone has shown to be the most reactive solvent towards POF due to its fastest etching rate compared to MIBK and acetone-methanol mixture. The POF is immersed and lifted from the solution for a specific time, depending on the power loss properties for the purpose of producing unclad POF. In comparison to silica fiber optic, the advantages of POF in terms of its simple technique and easy handling enable it to produce unclad POF without damaging the core region. The surface roughness of the POF is investigated under the microscope after being immersed into different solvent. This method of chemical tapering of POF can be used as the fundamental technique for sensor development. Next, the unclad fiber is immersed into ethanol solutions in order to determine the reaction of unclad POF towards its surrounding. The findings show that this particular sensor is sensitive towards concentration changes ranging between 10 wt% to 50 wt%. The Authors, published by EDP Sciences, 2017.